Perks and perils of adult learners in Communication English learning at English language centers in Vietnam - Hoa Minh Truong (English Language Teaching Educational Journal, 2021)
The teaching and learning of Communication English for adult learners is unlike that for children. Understanding of the differences between adult learners’ and young learners’ traits is considered a must for all English teachers so as to provide appropriate teaching methods and materials for adult learners in Communication English learning. Thus, this mixed-methods survey was conducted to investigate adult learners’ perks and perils in Communication English learning and suggested solutions for their better communicative performance. The sample of this study consisted of 148 adult learners from the five selected language centers in Ho Chi Minh City, Vietnam. Data were collected from questionnaire copies. The findings revealed that the adult learners had some perks including strong motivation, clear learning goal, good learner autonomy and able technology use for learning, or positive attitudes towards the existing teachers’ quality. Besides, some perils among these adult learners were sought, including low self-confidence, short time investment, and limited speaking practice environment. At last, they expected their teachers to make the lessons more interesting and realistic, and hoped their language centers to invite native language teachers.